The Effect of Performance Monitoring and Evaluation on Productivity Work of Village Devices in All District Villages Belitang Mulya - Rismansyah, Rismansyah; Salita, Shelen Mayang; Valianti, Reva Maria (prodima@fe.uika-bogor.ac.id, 2023)
Human resources are the most important factor in an organization as the holder of control and the main asset to achieve goals in the organization where he works. The phenomenon that occurs is that village officials are less disciplined when working, village officials come and go not according to the rules of working hours, lack of communication between col-leagues when carrying out activities. This study aims to determine the effect of monitoring and performance evaluation on the work productivity of village officials in all villages in the Belitang Mulya District. The research method used is quantitative. Data were analyzed using Simple Linear Regression, Multiple Linear Regression, Correlation Coefficient, Coefficient of Determination, t-Test, and F Test. The results showed that there was a signif-icant effect of performance evaluation on work productivity and there was a significant effect of monitoring and evaluation of performance on work productivity.